ANALISA DAN PERANCANGAN SISTEM E-REGISTRATION DALAM PENERIMAAN SISWA BARU BERBASIS WEB PADA SMK MULTIMEDIA MANDIRI AL-KAMAL - Muhammad Yuli Santoso; Ahmad Fikri Zulfikar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
In entering the modern era and the rapid development of technology today, humans recognize increasingly advanced and affordable technology to make it easier to carry out various activities in life. Technological advances are very rapid in various fields, for example in the fields of transportation, communication, health, education, and other fields so that people increasingly need technology to facilitate all the work in this life. Implementation of New Student Admission or E-Registration is one of the processes that exist in educational institutions such as schools that are useful for screening prospective students who are selected according to the criteria determined by the school to become their students. In general, the process of accepting new students is carried out through the stages of registration, selection tests, and announcements of student admissions. In this study, the application of the MultiMedia Mandiri Al-Kamal Vocational School which has been done manually so far, which allows there to be a lot of data shortages, is calculating test scores manually which allows errors to occur. The problem formulation of this research is how to create an information system for new student admissions at SMK MultiMedia Mandiri Al-Kamal. The research method used is literature, observation, analysis, design, testing and implementation. This new admissions information system was built using the PHP programming language and utilizes the MySQL database as a database server. The result of this research is a web-based admissions information system that has the ability to make it easy for parents of prospective new students to obtain all information about new student admissions and carry out the online registration process.